Efisiensi perbankan Islam di Asia Tenggara - Faaza Fakhrunnas (Faculty of Economics, Universitas Islam Indonesia, 2017)
The development of Islamic banks in Southeast Asia increases quickly. To measure the Islamic banking performance, Islamic banking efficiency can be adopted as a benchmark. This study aims to measure the efficiency of Islamic banks in Southeast Asia. By applying Stochastic Frontier Analysis, this study utilizes input variable comprising total deposit and operating cost, then output variable consisting to total financing and earning asset whereas all variables mentioned-above are put as independent variable. Moreover, total cost is posited as dependent variable. By observing 28 Islamic banks in Southeast Asia during 2009-2012, this research finds that the level of efficiency Islamic Bank in Malaysia is 94,04%, Brunei Darussalam is 88,59%, and Indonesia is 88,35%. By performing independent t-test, it shows that there has different efficiency between Islamic Bank in Indonesia and Malaysia, and also between Indonesia and Southeast Asia.